Pengembangan Aplikasi National Early Warning Score 2 (NEWS2) Berbasis Web dalam Penilaian Awal Pasien dengan Penyakit Akut - Joko Tri Wahyudi; Arif Fadillah; Dhia Ritaj Ramadhani (Masker Medika, 2023)
Background: Early Warning Score (EWS) is an early warning system that uses scoring to assess worsening patient conditions and improve overall emergency management. The EWS was also developed as a guide for rapid assessment and early diagnosis of acute illness in hospitalized patients. It is intended to be a tracking and trigger tool for consistent assessment of disease severity and to provide a useful baseline for evaluating a patient's clinical progress. In this digital era, there is another form of EWS, namely the National Early Warning Score 2 which has been issued by The Royal College of Physicians of London and has become a standardized assessment of the severity of acute illness in England's Nation Health Service (NHS), United Kingdom. The use of a web-based application in implementing NEWS2 is expected to increase the effectiveness of assessing the initial deterioration of patients in the ER. Purpose: This study aims to develop a web-based NEWS2 application in the initial assessment of patients with acute illness. Methods: This study is a Research and Development (R&D) study in an effort to develop a web-based NEWS 2 application and was tested on 4 patients at Muhammadiyah Hospital Palembang. Results: The web-based NEWS2 application has been successfully developed with the application address at https://appnews2.com and has been tested on 4 respondents at Muhammadiyah Palembang Hospital with a successful test status. Conclusion: The NEWS2 application has been successfully developed and it is hoped that the effectiveness of its use can be further investigated compared to conventional methods.